Spring 1865 : The Closing Campaigns of the Civil War - Jamieson, Perry D. (Book collections on Project MUSE., 2015)
When Gen. Robert E. Lee fled from Petersburg and Richmond, Virginia, in April 1865, many observers did not realize that the Civil War had reached its nadir. A large number of Confederates, from Jefferson Davis down to the rank-and-file, were determined to continue fighting. Though Union successes had nearly extinguished the Confederacy's hope for an outright victory, the South still believed it could force the Union to grant a negotiated peace that would salvage some of its war aims. As evidence of the Confederacy's determination, two major Union campaigns, along with a number of smaller engag.